Kamu diplomasisi aracı olarak sağlık : koronavirüs çalışmalarının türkiye’nin yumuşak gücüne etkisi - Bedier, Aslıhan (My University, 2024)
Bu çalışma, Türkiye'nin kamu diplomasisi çerçevesinde sağlık diplomasisi alanında gerçekleştirdiği faaliyetleri koronavirüs ile mücadelesi özelinde değerlendirmiştir. İlk üç dalga döneminde Türkiye ile ilgili İngilizce yayın yapan haber sitelerinde çıkan haberler van Dijk’ın söylem analiz modeline göre incelenmiş ve konuyla doğrudan ilgiili kişilerle yapılan mülakatlar aracılığıyla ülkenin yumuşak gücüne etkisi değerlendirilmiştir. Sağlık diplomasisi, yeni bir kamu diplomasisi aracı olarak son yirmi yılda sağlık alanında iş birliği ve insani yardım projelerinde Türkiye'nin önemli bir ivme kazandığını ortaya koymaktadır. Bu çalışmalar, uluslararası ilişkiler, hukuk, ekonomi ve halk sağlığı alanlarında yoğunlaşmış, konuyu kamu diplomasisi perspektifinden interdisipliner bir bakış açısıyla ele alan çalışmalar görece azdır. Bu çalışmada, sağlık diplomasisinin Türk kamu diplomasisindeki yeri, koronavirüs özelinde dış basında ele alınma şekli ve konunun paydaşları tarafından aktarılma biçimiyle dış politika, güç, kamu diplomasisi, marka, imaj ve sağlık perspektifinden holistik bakış açısıyla ele alınmıştır. Türkiye'nin özellikle 21. yüzyılda, girişimci ve insani politikalarla öne çıkan yumuşak güç potansiyeli ülkenin kamu diplomasisi alanında konumunu daha da güçlendirmesine olanak tanımıştır. Buna rağmen Türkiye ile ilgili çıkan koronavirüs haberleri eleştirel söylem analizine göre değerlendirildiğinde, ülkenin son yirmi yılda değişen ve gelişen siyasi, ekonomik, sosyal gelişmelerine karşılık haberlerde üçüncü dünya ülkesi kurgusunun ve buna bağlı söylemlerin üretildiği tespit edilmiş, haberlerin içeriğinde ve illüstrasyonlarında geri kalmış, anti-demokratik, totaliter rejim vurguları tespit edilmiştir. Örneklemde listelenen 86 farklı haber sitesinden derlenen toplam 235 haberde, olumsuz içerikli haberlerin oransal olarak daha fazla olduğu görülmüştür. Bu haberlerde illüstrasyon olarak kullanılan 183 fotoğraflı içerik olumsuz ve bilgilendirici nitelik olacak şekilde ayrıştırılmış ve genel itibariyle 85 haberin olumsuz olduğu tespit edilmiştir. Araştırmanın ikinci ayağını oluşturan mülakatlarda, katılımcıların onda dokuzu Türkiye’nin pandemiyle mücadelede gösterdiği performansı başarılı değerlendirmiş, sağlığın bir dış politika aracı olarak Türkiye için bir yumuşak güç kaynağı olduğuna yönelik görüş birliği oluşturmuştur.

This research investigates the effectiveness of Turkey's health diplomacy tactics within its public diplomacy strategy during the coronavirus outbreak. Employing van Dijk's discourse analysis model, news coverage of Turkey in English-language media outlets during the first three waves was analyzed. To assess the impact on the country's soft power, interviews were conducted with relevant stakeholders. The emergence of health diplomacy as a novel public diplomacy tool presents a compelling case for examining Turkey's growing prominence in health cooperation and humanitarian aid initiatives over the past two decades. Existing scholarship on this topic primarily resides within the siloed disciplines of international relations, law, economics, and public health. This study aims to contribute a fresh perspective by employing an interdisciplinary lens, specifically focusing on public diplomacy. It delves into the strategic positioning of health diplomacy within Turkey's broader public diplomacy efforts. The analysis then investigates the portrayal of Turkey's response to the COVID-19 pandemic, particularly within the foreign press. Finally, the study adopts a holistic approach, meticulously examining the narratives employed by various stakeholders – encompassing foreign policy actors, power dynamics, public diplomacy strategies, national branding considerations, and the crafting of Turkey's international image – all viewed through the prism of health. Turkey's rise in soft power, particularly through its entrepreneurial and humanitarian initiatives in the 21st century, has demonstrably bolstered its public diplomacy efforts. However, critical discourse analysis of COVID-19 news coverage regarding Turkey reveals a constructed narrative portraying it as a 'third-world country.' This discursive strategy is argued to be a response to Turkey's significant political, economic, and social transformations over the past two decades. The analysis further highlights underdeveloped content and imagery in the news, alongside an emphasis on anti-democratic and totalitarian regimes. A content analysis of 235 news articles from 86 diverse sources revealed a predominance of negative portrayals concerning Turkey's handling of the pandemic. This negativity extended to the accompanying visuals, with 85 news items featuring predominantly negative imagery. Conversely, interviews conducted in the second phase indicated a contrasting perspective: 90% of participants expressed satisfaction with Turkey's pandemic response and acknowledged the nation's utilization of healthcare as a form of soft power in foreign policy.
Health, as a tool of public diplomacy : the effect of Turkiye’s performance during the COVID-19 pandemİc to its public diplomacy
Keywords: COVID-19 Pandemic, 2020; COVID-19 pandemisi, 2020; health diplomacy; kamu diplomasisi Coronavirus; Koronavirüs; Political aspects; public diplomacy; sağlık diplomasisi; Siyasi yönleri; soft power; Turkey; Türkiye; yumuşak güç